2023
DOI: 10.1101/2023.10.09.561166
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in electrophysiological aperiodic activity during cognitive control in Parkinson’s disease

Noémie Monchy,
Julien Modolo,
Jean-François Houvenaghel
et al.

Abstract: Cognitive symptoms in Parkinson's disease (PD) are common and can significantly affect quality of life. Therefore, there is an urgent clinical need to identify a signature derived from behavioral and/or neuroimaging indicators that could predict which patients are at increased risk for early and rapid cognitive decline. Recently, converging evidence identified electroencephalogram (EEG) aperiodic activity as meaningful physiological information associated with age, development, cognitive and perceptual states … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…Voytek et al, 2015;Thuwal et al, 2021;Akbarian et al, 2023), but the evidence remains inconclusive, as some studies have reported contrasting results (e.g. Monchy et al, 2023)). The discrepancy highlights the need for further research to understand how different factors influence the manifestation of the aperiodic component as a reflection of cognitive processes.…”
Section: Interplay Of Periodic and Aperiodic Eeg Componentsmentioning
confidence: 99%
“…Voytek et al, 2015;Thuwal et al, 2021;Akbarian et al, 2023), but the evidence remains inconclusive, as some studies have reported contrasting results (e.g. Monchy et al, 2023)). The discrepancy highlights the need for further research to understand how different factors influence the manifestation of the aperiodic component as a reflection of cognitive processes.…”
Section: Interplay Of Periodic and Aperiodic Eeg Componentsmentioning
confidence: 99%
“…Parameterizing the neural signal into oscillatory and aperiodic components allows investigators to account for broadband shifts in power across frequencies (offset), the structure of aperiodic power across the spectrum (exponent), and detect peaks of oscillatory power above the aperiodic activity that cannot be isolated within traditional canonical power frequency bands. 32 , 34 Thus, given the conflicting reports of changes in spectral power post-mTBI, parameterization of EEG scalp recordings across frequencies, though accounting for the aperiodic signal, may be an important analytical step to develop a greater understanding of the neuroplastic rhythmic and arrhythmic changes in brain activity post-mTBI.…”
Section: Introductionmentioning
confidence: 99%